Storm Daria: Societal and energy impacts in northwest Europe on 25–26 January 1990 - A. J. Kettle (Advances in Geosciences)
Between late January and early March of 1990 Europe was hit by a sequence of severe winter storms that caused significant infrastructure damage and a large number fatalities. The storm sequence started with Hurricane Daria on 25–26 January 1990, which was one of the most serious events of the storm cluster, especially for the UK. The low pressure centre moved in a west-northwest direction across Ireland, southern Scotland, and north of Denmark before moving further into the Baltic. The strongest winds south of the trajectory path caused significant damage and disruptions in England, France, Belgium, the Netherlands, and West Germany. Media reports highlighted building damage, interrupted transportation networks, power outages, and fatalities. There were also a series of maritime emergencies in the Bay of Biscay, English Channel, North Sea, and Baltic Sea. This contribution takes a closer look at Storm Daria, presenting an overview of meteorological measurements and the societal impacts, followed by an analysis of the North Sea tide gauge network to understand the storm surge and possible large wave occurrences. Offshore wind energy was at the planning stage in this early period, but onshore wind energy was established in Denmark with demonstration projects in other countries. The storm is an important case study of extreme meteorological conditions that can impact energy infrastructure.